Validation of the scholastic aptitude test for use in the selection of applicants for primary teachers training institutions in Bangkok and Dhonburi, Thailand - Preechabhan, Tinakorn 1933- ([Quezon City s.n.], 1964)
This study is concerned with the assessment of the effectiveness of a scholastic aptitude test in predicting the students' performance in college activity as this test has been specially devised in view of selecting student teachers who have the potential for success in their chosen sphere of work in Thailand.
Thesis (M.Ed.)--University of the Philippines
Keywords: Mental test